Cultural Diplomacy in Films by Garin Nugroho - Muhammad Abdul Aziz Arif Bawono; Saleh, Sukmawati (PANTUN: Jurnal Ilmiah Seni Budaya, 2024)
This article conducts an in-depth examination of Indonesian cultural elements in Garin Nugroho’s films, using Joseph Nye’s theory of cultural diplomacy as a conceptual framework. Through the analysis of films such as “Daun Di Atas Bantal” and “Opera Jawa,” the article aims to identify and explore the local cultural elements that Nugroho integrates into his film narratives. This research focuses on how Garin Nugroho presents traditional Indonesian cultural elements and how this contributes to international understanding of Indonesia’s cultural richness. By applying the theory of cultural diplomacy, the article highlights the importance of cultural representation in films as a form of soft power capable of building a positive image of Indonesia on the global stage. The study also discusses how Garin Nugroho’s films play a role in cultural diplomacy, serving not only as a medium of entertainment but also as an educational tool and cultural promotion. The article supports the hypothesis that cultural diplomacy plays a crucial role in building understanding and appreciation of a nation’s cultural wealth, as well as strengthening international relations through cultural exchange. Thus, this article functions not only as a critical analysis of Garin Nugroho’s films but also as a case study demonstrating how cultural diplomacy can be effectively used to promote and introduce Indonesian culture to international audiences. The findings of this research are expected to contribute to film studies, cultural diplomacy, and the development of future strategies for promoting Indonesian culture.